Probiotics, Encompassing Lactic Acid Bacteria, Are Perpetually Updated In Their Attributes And Significance In Human Health (International Journal of Environmental Sciences, 2025)
The gut contains over 100 trillion microorganisms, including probiotics, which maintain physiological homeostasis. Probiotics must be human-safe, resistant to stomach acid, bile salts, and pancreatic juice, and survive in suitable concentrations to provide health benefits. Bile affects intestinal bacteria's function, suggesting isolated strains of bacteria could be potential probiotic cultures for food industries. Lactobacilli, a crucial group, can inhibit harmful microflora and restore gut flora, with these isolated strains showing excellent potential.